Pengaruh Corporate Governance terhadap Pengungkapan Emisi Gas Rumah Kaca dengan Peran Audit Internal sebagai Pemoderasi - Grediani, Evi; Yustrianthe, Rahmawati Hanny; Niandari, Nanik (Universitas Pendidikan Ganesha, 2020)
This study aims at internal audit reasons that moderate the effect of corporate governance on the level of disclosure of greenhouse gas (GHG) emissions. The sample selection technique was purposive sampling of 41 companies listed on the Indonesia Stock Exchange for the period 2015-2018 which made complete sustainable reports so that a total of 164 observations were made. Using multiple linear regression to test the hypothesis, the results of the study found that the proportion of female commissioners, board size and audit committee size significantly affects the disclosure of greenhouse gas emissions. Likewise, the role of internal audit significantly strengthens the influence between corporate governance and disclosure of greenhouse gas emissions. Other results indicate that the proportion of members of the independent board of commissioners and the frequency of audit committee meetings are not able to influence the disclosure of greenhouse gas emissions.